A single‐cell RNA labeling strategy for measuring stress response upon tissue dissociation - Anika Neuschulz; Olga Bakina; Victor Badillo‐Lisakowski; Pedro Olivares‐Chauvet; Thomas Conrad; Michael Gotthardt; Helmut Kettenmann; Jan Philipp Junker (Molecular Systems Biology)
Abstract Tissue dissociation, a crucial step in single‐cell sample preparation, can alter the transcriptional state of a sample through the intrinsic cellular stress response. Here we demonstrate a general approach for measuring transcriptional response during sample preparation. In our method, transcripts made during dissociation are labeled for later identification upon sequencing. We found general as well as cell‐type‐specific dissociation response programs in zebrafish larvae, and we observed sample‐to‐sample variation in the dissociation response of mouse cardiomyocytes despite well‐controlled experimental conditions. Finally, we showed that dissociation of the mouse hippocampus can lead to the artificial activation of microglia. In summary, our approach facilitates experimental optimization of dissociation procedures as well as computational removal of transcriptional perturbation response.